Assessment of resistance patterns of antimicrobials with high importance in human health, in diagnosed bovine neumonia - de Yaniz, María Guadalupe (2019)
Bovine respiratory disease (BRD) is themost important illness in feedlot cattle, where animals aresubjected to high pharmacological pressure with antimicrobial(ATM) drugs for prevention or treatment. Some of ATM used forprevention or treatment of BRD, are considered by OMS as veryhigh and high importance for human health. The aim of thisstudy was to assess the resistance frequency of Pasteurellamultocida and Mannheimia haemolytica isolated from dead cattlewith BRD, in order to determine the bacterial resistance. Thistrial involved the analysis of 41 isolated strains from 38 deadanimals. Antimicrobial susceptibility testing was performed on allisolates strains using broth microdilution and a commerciallyavailable bovine/porcine panel (Sensititre®; Trek DiagnosticSystems, Cleveland, OH, USA). The frequency of resistance forthe group I of antimicrobials (agents of very high importance tohuman health-Fluorquinolones and 3rd generation ofCephalospirines) was a 0% for the 2 bacteria assayed. However,the frequency of resistance for Category II antimicrobials (highimportance to human health?aminoglycosides, macrolides andlincosamides) was variable. Thus, the resistance pattern obtainedfor clindamycin was 47.6 and 55 % for either P. multocida andM. haemolytica, whilst for tilosyn was 19 and 100 %,respectively. The 21.9 % of the strains analyzed did not showresistance to any class of the antimicrobials tested. Regardingthe multiresistance pattern, the 26.9 % of the strains showedresistance to only one antimicrobial group while the 51.2 % ofthe strains showed resistance to 2-4 antimicrobials. M.haemolytica resulted the bacteria with the highest resistancelevels in animals died by BRD disease. The determination of thefrequency of resistance pattern is essential to rationalize thetherapeutic in animals subjected to high pharmacologicalpressure, in order to design new treatment interventions forreducing the development of bacterial resistance.